2005
DOI: 10.2320/matertrans.46.1026
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Hydrogen Permeability of Nb-Ti-Ni Alloys with High Resistance to Hydrogen Embrittlement

Abstract: Microstructures and hydrogen permeability (È) of as-cast Nb-Ti-Ni alloys have been investigated by scanning electron microscopy (SEM) and by the gas permeation technique, respectively. The È value increases with increasing temperature and the amount of the Nb content for every alloy. In these alloys, the Nb 39 Ti 31 Ni 30 alloy, consisting of the primary bcc-(Nb, Ti) solid solution and the eutectic {(Nb, Ti)+TiNi} phase, shows the highest È, which is equivalent to that of Pd. On the other hand, the Nb 10 Ti 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 14 publications
1
46
0
1
Order By: Relevance
“…The hydrogen permeability of the Nb-Ti-Ni alloy increases with the volume fraction of the primary (Nb, Ti) phase. 4,5) On the other hand, the Nb-Ti-Co alloy with the eutectic composition possesses the highest hydrogen permeability among all the Nb-Ti-Co ternary alloys. 6) This indicates that hydrogen permeability depends on the alloy systems and their compositions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen permeability of the Nb-Ti-Ni alloy increases with the volume fraction of the primary (Nb, Ti) phase. 4,5) On the other hand, the Nb-Ti-Co alloy with the eutectic composition possesses the highest hydrogen permeability among all the Nb-Ti-Co ternary alloys. 6) This indicates that hydrogen permeability depends on the alloy systems and their compositions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, one of the authors found out that the Nb-Ti-Ni alloy consists of bcc-(Nb, Ti) + B2-TiNi eutectic microstructures with an appropriate combination of high-hydrogen permeability and excellent hydrogen embrittlement resistance. 4,5) The former property is attributable to the bcc-(Nb, Ti) phase, while the latter property is attributable to the B2-TiNi phase in the eutectic structure. On the basis of the same concept, Nb-Ti-Co, 6) Nb-Zr-Ni 7,8) and Nb-Zr-Co alloys have been developed as new hydrogen permeation materials.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental procedure has been described in detail elsewhere. 10,11) 3. Results and Discussion Figure 1 shows the temperature dependence of hydrogen permeability È for the as-cast Nb 40 Ti x Zr 12 Ni 48Àx alloys (x ¼ 14, 18, 20, 22 and 24) in the form of an Arrhenius plot.…”
Section: Methodsmentioning
confidence: 99%
“…Some groups have tried to develop new alloys such as V-based alloys, 3,4) Nb-based alloys, 5,6) amorphous Zr-Ni alloys, 7) amorphous Zr-Ni-Nb alloys, 8,9) and so on. 10,11) However, the overcoming of the hydrogen embrittlement in these alloys is insufficient. Recently, the present authors have developed new non-Pd based hydrogen permeation alloys such as the Nb-TiNi, 10) the Nb-TiCo 11) and the Nb-ZrNi ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation